Do hurricanes matter?: A case study of the residential real estate market in Brunswick County, North Carolina. Issue 3 (5th June 2017) - Saginor, Jesse; Ge, Yue
Abstract : Purpose: The purpose of this research is to analyze a county's housing market over 23 years to determine what impact, if any, multiple hurricanes have had on the residential real estate market. Design/methodology/approach: This research uses a hedonic price model to determine the impacts that multiple hurricanes had on housing values. Findings: There was a significant and negative countywide impact on housing sales values in the 1996, which can directly be attributed to three hurricanes impacting Brunswick County. Economic factors, rather than hurricanes and related storms, are more likely to impact sales values in all other years. Research limitations/implications: This research is limited only to single-family home sales in Brunswick County, North Carolina, from 1984 to 2007. The model does not include multi-family residential uses. Practical implications: Unlike many other areas that have been studied regarding natural disasters, Brunswick County has been hit multiple times by hurricanes and related storms, providing some insight into the long-term implications of the impact of storms on housing values over an extended period of time. The practical implication is that despite the likelihood of hurricanes and proximity to the ocean, people are willing to pay to live in coastal areas, even an area with a history of repeated direct and indirect strikes by hurricanes. Originality/value: Unlike much of the peer-reviewed research that looks at a single occurrence of a natural disaster, this research looks at the impacts of multiple hurricanes on a single county over 23 years to determine what impact, if any, these storms have on the overall housing market.